INTERDISCIPLINARITY APPROACHES IN CONTEXT OF COMPLEX INTRAORAL REHABILITATON TREATMENT AT YOUNG PACIENTS WITH SOCIAL ANXIETY -CLINICAL EXAMINATION -PART 1 - Lucian Stefan Burlea; Laura Elisabeta Checherita; Ovidiu Stamatin; Ioana Rudnic; Onofrei Bianca Andreea; Magda Barleanu; Magda Cuciureanu; Maria Antonela Beldiman; Ana Maria Ciubara; Elena Mihaela Carausu; Liana Aminov (Romanian Society of Oral Rehabilitation, 2023)
Social anxiety is one of the most common psychological disorders along with depression and generalized anxiety. Avoiding eye contact, persistent fear of being judged and negatively evaluated by others, and social isolation are just some of the specific features of this type of anxiety.As part of the complex oral rehabilitation treatment, we also faced such a case which involved a lot of attention and time, but to which was also added the joint and muscle pathology, superposing with the social the dental treatments anxiety , the patient needing a special complex treatment approach.